The prevalence, awareness, management and control of hypertension in men and women in Benin, West Africa: the TAHES study - Ileana Desormais (BMC Cardiovascular Disorders, 2019)
Abstract Background Due to epidemiological transitions, Sub-Saharan Africa is facing a growing burden of non-communicable diseases, including cardiovascular diseases (CVDs). Among their risk factors, hypertension is a major determinant of CVDs, but the prevalence and level of awareness and management of this condition are poorly studied in African populations. The aim of this study was to determine the prevalence of hypertension and identify its associated risk factors as well as the awareness and management of this condition in a community-dwelling cohort in Benin. Methods A cross-sectional door-to-door study was conducted in the population over the age of 25 years in Tanve, a rural setting in Benin. The questionnaire and anthropometric measurements of the World Health Organization STEPWISE survey were used. Blood pressure was measured using standard procedures. Results The sample included 1777 subjects (60.9% females, mean age was 42.5 ± 16.5 years). The prevalence of hypertension was 32.9%, similar in men (32.8%) and women (33.0%, p = 0.9342). Age and obesity were significantly associated with hypertension. Less than half (42%) of hypertensive people were aware about their condition and only 46.3% of them were treated. Awareness ratios differed between men and women (respectively 32.9% vs. 47.5%; p = 0.0039) and was not influenced by age, education, occupation, marital status or income. Female sex was the only factor associated with better controlled HTN, independent of socio-economic parameters. Conclusion This large population-based study confirms the high prevalence, low awareness, and low control of hypertension in men and women in sub-Saharan Africa. Only half of the populations with hypertension are aware of their hypertension, indicating a high burden of undiagnosed and un-controlled high blood pressure in these populations.